Perbandingan penguasaan kosakata siswa menggunakan wordwall.net dan kahoot pada siswa yang berbeda minat : kosakata siswa - Rahma Wahidha; Julia Anugerah Putri; Arif Miboy (Universitas Muhammadiyah Surabaya, 2025)
This study aimed at examining the comparation of students’vocabulary mastery using wordwall.net and kahoot with students different interests. The objectives of the study were, to analyze high and low interests students’ score of vocabulary in order to explain the effectiveness of Wordwall.Net , to analyze high and low interests students’ score of vocabulary in order to explain the effectiveness of Kahoot, to analyze the significant difference between the students with high interests after being taught by using wordwall.Net and Kahoot for learning vocabulary, to analyze the significant difference between the students with low interests after being taught by using wordwall.Net and Kahoot for learning vocabulary, to analyze how the interaction is among teaching, students’ interests and vocabulary. It was an experimental research with 2x2 factorial design. Questionnaire, observation and test were used. The data from questionnaire and vocabulary test were analyzed quantitatively using T-test and ANOVA.The results of this research showed that Kahoot! to students with high and low interests (79.17 and 57.50) and Woerdwall.net to students with high and low interests (85.50 and 62.86) are effective The mean score vocabulary of students using Wordwall.net multimedia is higher than Kahoot! in teaching vocabulary There was no significant interaction among the use of multimedia, students’ interests and students’ vocabulary achievement